Carbon release through abrupt permafrost thaw - Turetsky Merritt R; Abbott, Benjamin W; Jones, Miriam C; Walter, Anthony Katey; Olefeldt, David; Schuur, Edward A; Grosse Guido; Kuhry, Peter; Hugelius Gustaf; Koven, Charles; Lawrence, David M; Gibson, Carolyn; et al. (Nature geoscience, 2020)
The permafrost zone is expected to be a substantial carbon source to the atmosphere, yet large-scale models currently only simulate gradual changes in seasonally thawed soil. Abrupt thaw will probably occur in <20% of the permafrost zone but could affect half of permafrost carbon through collapsing ground, rapid erosion and landslides. Here, we synthesize the best available information and develop inventory models to simulate abrupt thaw impacts on permafrost carbon balance. Emissions across 2.5 million km2 of abrupt thaw could provide a similar climate feedback as gradual thaw emissions from the entire 18 million km2 permafrost region under the warming projection of Representative Concentration Pathway 8.5. While models forecast that gradual thaw may lead to net ecosystem carbon uptake under projections of Representative Concentration Pathway 4.5, abrupt thaw emissions are likely to offset this potential carbon sink. Active hillslope erosional features will occupy 3% of abrupt thaw terrain by 2300 but emit one-third of abrupt thaw carbon losses. Thaw lakes and wetlands are methane hot spots but their carbon release is partially offset by slowly regrowing vegetation. After considering abrupt thaw stabilization, lake drainage and soil carbon uptake by vegetation regrowth, we conclude that models considering only gradual permafrost thaw are substantially underestimating carbon emissions from thawing permafrost.Analyses of inventory models under two climate change projection scenarios suggest that carbon emissions from abrupt thaw of permafrost through ground collapse, erosion and landslides could contribute significantly to the overall permafrost carbon balance.